Resonant raman scattering in CdSxSe1-x nanocrystals : effects of phonon confinement, composition and elastic strain - Freitas Neto, E. S. (2011)
Optical phonon modes confined in CdSxSe1-x nanocrystal (NC) quantum dots (≈ 2 nm in radius) grown in a glass matrix by the melting-nucleation method, were studied by means of resonant Raman scattering (RRS)spectroscopy and theoretical modelling. The formation of nanocrystalline quantum dots (QDs) is evidenced by the observation of absorption peaks and theoretically expected resonance bands in the RRS excitation spectra. Since the underlying material is a ternary alloy, this system offers the possibility to investigate the nterplay between the effects of phonon localization by disorder and phonon confinement by the NC/matrix interface. Based on the concept of propagating optical phonons, accepted for two-mode pseudo-binary alloys in their bulk form, we extended the continuous lattice dynamics model that has successfully been used for nearly-spherical NCs of binary materials, to the present case. After determining the alloy composition for NCs (that can be evaluated with only 2-3% uncertainty using the bulk longitudinal optical phonon frequencies) and the NC size (using atomic force microscopy and optical absorption data), the experimental RRS spectra were described rather well by this theory, including the lineshape and polarization dependence of the scattering intensity. Even though the presence of a compressive strain in the NCs, introduced by the matrix masks the expected downward shift owing to the phonons’ spatial quantization, the asymmetric broadening of both Raman peaks is similar to that characteristic of NCs of pure binary materials. Although with some caution, we suggest that both CdSe-like and CdS-like optical phonon modes indeed are propagating within the NC size (and not localized by disorder at a shorter length scale) unless the alloy is considerably heterogeneous.